Eggshell membrane: A possible new natural therapeutic for joint and connective tissue disorders. Results from two open-label human clinical studies - Kevin J Ruff (Dove Medical Press, 2009)
Kevin J Ruff1, Dale P DeVore2, Michael D Leu3, Mark A Robinson41ESM Technologies, LLC, Carthage, MO, USA; 2Membrell, LLC, Carthage, MO, USA; 3Private Practice, Jenks, OK, USA; 4Robinson Family Health Center, Carthage, MO, USABackground: Natural Eggshell Membrane (NEM®) is a novel dietary supplement that contains naturally occurring glycosaminoglycans and proteins essential for maintaining healthy joint and connective tissues. Two single center, open-label human clinical studies were conducted to evaluate the efficacy and safety of NEM® as a treatment for pain and inflexibility associated with joint and connective tissue disorders. Methods: Eleven (single-arm trial) and 28 (double-arm trial) patients received oral NEM® 500 mg once daily for four weeks. The primary outcome measure was to evaluate the change in general pain associated with the treatment joints/areas (both studies). In the single-arm trial, range of motion (ROM) and related ROM-associated pain was also evaluated. The primary treatment response endpoints were at seven and 30 days. Both clinical assessments were performed on the intent-to-treat (ITT) population within each study.Results: Single-arm trial: Supplementation with NEM® produced a significant treatment response at seven days for flexibility (27.8% increase; P = 0.038) and at 30 days for general pain (72.5% reduction; P = 0.007), flexibility (43.7% increase; P = 0.006), and ROM-associated pain (75.9% reduction; P = 0.021). Double-arm trial: Supplementation with NEM® produced a significant treatment response for pain at seven days for both treatment arms (X: 18.4% reduction; P = 0.021. Y: 31.3% reduction; P = 0.014). There was no clinically meaningful difference between treatment arms at seven days, so the Y arm crossed over to the X formulation for the remainder of the study. The significant treatment response continued through 30 days for pain (30.2% reduction; P = 0.0001). There were no adverse events reported during either study and the treatment was reported to be well tolerated by study participants. Conclusions: Natural Eggshell Membrane (NEM®) is a possible new effective and safe therapeutic option for the treatment of pain and inflexibility associated with joint and connective tissue (JCT) disorders. Supplementation with NEM®, 500 mg taken once daily, significantly reduced pain, both rapidly (seven days) and continuously (30 days). It also showed clinically meaningful results from a brief responder analysis, demonstrating that significant proportions of treated patients may be helped considerably from NEM® supplementation. The Clinical Trial Registration numbers for these trials are: NCT00750230 and NCT00750854.Keywords: arthritis, pain, stiffness, eggshell membrane, joint, connective tissue, complimentary, alternative